THE ORIGIN OF LAYER-BY-LAYER ALTERNATION OF CUBIC AND HEXAGONAL SYMMETRY IN NATURAL AND SYNTHETIC NOBLE OPAL STRUCTURE - Kalinin D.V.; Plekhanov A.I.; Vosel S.V.; Sobolev N.V. (My University, 2003)
In suspensions of monodispersed spherical silica particles (MSSP) proceeds their sedimentation with formation of semi-liquid supramolecular crystals (SC). Solid MSSP in them are separated by liquid layers of a thickness near two ionic atmospheres. SC transformation to solid noble opal structures in nature and experiment is associated with liquid removal and transition to the structure with direct coagulation contact of MSSP surfaces. Presented are experimental data determining the causes and mechanism of the described processes. These data enabled to understand for the first time the origin of alternation of layers and packs with different symmetry in opal structure.